2007
DOI: 10.4161/cbt.6.3.3663
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of RhoE in non-small cell lung cancer (NSCLC) is associated with smoking and correlates with DNA copy number changes

Abstract: RhoE, a small G protein, is constitutively GTP bound within the cell and can regulate actin cytoskeleton reorganization, leading to the appearance of aggregates of actin filaments. Although emerging evidence suggests that RhoE is causally involved in cancer formation and progression, little is known about its significance in solid cancer, including lung cancer. In the present study, the expression of RhoE was analyzed using Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR), real-time RT-PCR, immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…In the non-small cell lung cancer tissues, the expression of Rnd3, mRNA, and protein levels were dramatically increased, compared to that of adjacent non-tumoral lung tissues. Moreover, overexpression of Rnd3 was correlated to patients’ smoking history [36]. Together with our study, overexpression of Rnd3 in lung tissue could be induced by environmental stresses.…”
Section: Discussionsupporting
confidence: 75%
“…In the non-small cell lung cancer tissues, the expression of Rnd3, mRNA, and protein levels were dramatically increased, compared to that of adjacent non-tumoral lung tissues. Moreover, overexpression of Rnd3 was correlated to patients’ smoking history [36]. Together with our study, overexpression of Rnd3 in lung tissue could be induced by environmental stresses.…”
Section: Discussionsupporting
confidence: 75%
“…Interestingly, as a gene highly related to tumors, research on the role of Rnd3 in NSCLC is extremely deficient. Two studies showed that Rnd3 over-expression may be associated with an unfavorable prognosis in NSCLC patients [27], [28] while the precise role of Rnd3 in NSCLC has not yet been investigated. Here, we reported that Rnd3 is down-regulated in H358, H520 and A549 cells, and this down-regulation promotes the growth of these two cell lines and is dependent upon up-regulated Notch signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Our lab recently revealed that RND3 is substantially downregulated in glioblastoma multiform (GBM), and this downregulation is negatively associated with the clinical progression and prognosis of patients (manuscript submitted). However, results from non-small cell lung cancer (30, 148), colorectal carcinoma (153), pancreatic cancer (50), and gastric carcinoma (35) studies showed that high RND3 expression positively correlated with tumor progression. However, there is some controversy over the results from lung cancer and colorectal carcinoma observations.…”
Section: Tumormentioning
confidence: 99%